PRESERVATION OF FISH BY FREEZING AND GLAZING: I L KE PING QUALITY OF FISH WITH PARTICULAR REFERENCE TO YELLOW DISCOLOURATION AND OTHER ALLIED ORGANOLEPTIC CH.ANGES ON PROLONGED STORAGE - JADHAV, M G; MAGAR, N G (Fishery Technology, 2025)
Organoleptic observations of quick, slow and bloclc frozen,glazed and stored fish were recorded at regular intervals. Glazingwas renewed at intervals of four weeks. Development of yellowdiscolouration in the case of white pomfret was followed. Keepingquality of glazed fish was better than unglazed frozen fish. Yellowdiscolouration could be controlled by ascorbic acid for 4~ monthsand by a mixture of ~odium chloride and glucose for 5t months.